2014
DOI: 10.7860/jcdr/2014/11242.5335
|View full text |Cite
|
Sign up to set email alerts
|

Arnold Chiari Malformation with Spina Bifida: A Lost Opportunity of Folic Acid Supplementation

Abstract: In Arnold Chiari (kee-AHR-ee) II malformation elongated cerebellar tonsils are displaced inferiorly through the Foramen Magnum into the upper cervical spinal canal. It is a complex anomaly with skull, dura, brain, spine and cord manifestations. Meningomyelocele is seen in all cases. We present a case of type II Arnold Chiari Malformation diagnosed in utero in a pregnant lady .There was no periconceptional folic acid supplementation. As the role of the Methylene Tetra Hydro Folate Reductase gene polymorphism in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 8 publications
1
12
0
4
Order By: Relevance
“…Lee S et al [11] observed that ventriculomegaly was common (but no syrinx or scoliosis) was no.4). Basilar invaginations are found in 50% of cases of type II CM [14]. In the present study, basilar invagination was absent in type II CM (Table 5).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Lee S et al [11] observed that ventriculomegaly was common (but no syrinx or scoliosis) was no.4). Basilar invaginations are found in 50% of cases of type II CM [14]. In the present study, basilar invagination was absent in type II CM (Table 5).…”
Section: Discussionsupporting
confidence: 57%
“…In type II CM, moderate hydrocephalous has been documented in about 25% cases. Syringomyelia is present in 60% of established cases [14]. Among 14 type II CM patients in the present study, 28.57% were associated with hydrocephalus and 35.71% were associated with syringomyelia (Figure 2A, 2B).…”
Section: Discussionmentioning
confidence: 52%
“…There are also reports of neural tube defects, calvarial defects, fenestrated falx, hypoplastic tentorium, wider foramen magnum, medullary kink and corpus callosal hypoplasia. [5,6] It can be noted that in the present case, some of these defects were observed; there were other defects such as presence of a large cyst abutting spina bifida, dilated lateral ventricles and mild scoliosis are seldom associated with type II ACM.…”
Section: Case Reportmentioning
confidence: 51%
“…One of the most commonly performed treatment procedure is atlantoaxial stabilization [9]. In addition, there is a report that type II ACM can be prevented by preconceptional folic acid and Vitamin B 12 supplementation [5]. Complexity of disabilities involving wide range of neural and skeletal malformations, prenatal diagnosis of the malformation and possibility of medical termination of pregnancy as in the present case may be are some of the reasons for lack of abundancy about literature on treatments for type II ACM.…”
Section: Case Reportmentioning
confidence: 77%
See 1 more Smart Citation